CHANGE IN THE VOLTAGE OF A PN JUNCTION IN A MAGNETIC FIELD AT DIFFERENT TEMPERATURES (Scientific journal of the Fergana State University, 2026)
Technology plays a significant role in our lives today. Since p-n junction diodes and transistors are widely used in engineering, studying their parameters, sensitivity to external influences, and characteristics is highly relevant. This paper examines the influence of a magnetic field on the current-voltage characteristic, voltage, and potential barrier height of a p-n junction. It was experimentally discovered that with increasing magnetic field, the current-voltage characteristic shifts to the right, resistance increases, and voltage also increases, which is explained by the Hall effect. The increase in resistance is associated with the magnetoresistance effect. An expression is presented for the p-n junction voltage as a function of the magnetic field, as well as its change at different temperatures. It was experimentally discovered that with decreasing temperature, the voltage difference becomes large in the presence and absence of a magnetic field. An expression is presented describing the change in voltage depending on the magnetic field at low temperatures and in a strong magnetic field. The graphs obtained using this expression show that the voltage increases with decreasing temperature, as do the experimental results. To explain this dependence, we used the change in the Hall coefficient depending on charge carrier mobility. We then discovered that the Hall voltage also increases with decreasing temperature. Our results were close to the experimental ones. The obtained theoretical results were compared with the experimental ones, and conclusions were drawn.